Ravaged mandibular ramus: Two rare case presentations of unicystic ameloblastoma with a view on management - Justin Mathew; S Akhil; Jubin Thomas; Fousiya Ali (Wolters Kluwer Medknow Publications, 2022)
Unicystic ameloblastoma (UA) is a rare, slow-growing, persistent, locally invasive, and cystic variant of ameloblastoma. This article presents two different variants of UA. The first case was a rare presentation of UA in an 11-year-old patient involving the impacted second molar, which is otherwise usually associated with an impacted mandibular third molar. It was diagnosed with UA-luminal type and treated by a piezoelectric ultrasonic device with minimal trauma to soft tissue. The second one was associated with impacted mandibular third molar extending the entire ramus of mandible till the coronoid which was diagnosed with UA-mural type and treated by cystic enucleation with platelet-rich fibrin graft. Recurrence was not observed during a 6-month follow-up. The aim of this case presentation was to give an insight into the destructive nature of UA and its diagnosis and management to maxillofacial surgeons as well as dental practitioners.